THE IMPLEMENTATION OF WORD COOKIES APPS TO IMPROVE VOCABULARY MASTERY OF STUDENTS AT SEMARANG - Alfianto, Cindi Nurul; Theresia Cicik Sophia B.,S.S.,M.Pd; Ririn Ambarini, S.Pd.,M.Hum (CV. Mitkom Indotama, 2024)
Vocabulary is the most important language in the world. This quantitative study implemented word cookies apps to improve vocabulary mastery. In this study, the aim was to enhance students' vocabulary mastery in tenth grade at SMKN 9 Semarang and was to find out the result of students’ vocabulary mastery before and after using Word Cookies Apps and to find out whether there was any significant difference in students’ ability in their vocabulary mastery, to achieve the aim of this study, it used a pre-experimental design. The study was conducted in the tenth grade of SMKN 9 Semarang. A total of 36 students participated in this study. Data were collected from the pre-test, the post-test, and the documentation. An essay has been used as the instrument of this study. To determine the results of a significant difference in vocabulary mastery between students before and after they were taught using Word Cookies Apps, the data were analyzed using the t-test formula in the SPSS 25 program. The results of the pre-test were still low, the mean pre-test score was 61,78 and the category is fair. The lowest score pre-test was 40 and the highest was 78. The result of the post-test was a mean of 81,08 for the category good, the lowest score was 65, and the highest was 95. So it can be concluded the learning process results refer to the hypothesis when less than <0.05 is accepted, and if more than t >0.05 is rejected, the result is < 0.00 accepted. Based on this data, The researcher concluded that the implementation of Word Cookies Apps to improve vocabulary mastery could improve students’ vocabulary mastery.